Nonlinguistic Presupposition in Literary Translation: A Trend towards Dehistoricising, Deideologising and Depoliticising the Original - Abualadas , Othman (Dirasat: Human and Social Sciences, 2022)
This paper explores nonlinguistic (cultural) presupposition in Kilpatrick’s English translation of Ghassan Kanafani’s Arabic novel Men in the Sun. The goal is to see if the English translation (under the impact of global English) shifts the sociocultural knowledge presupposed in the original and thus alters its political and ideological messages. The analysis reveals a trend to lose nonlinguistic presupposition via translation, which is associated with the translator’s tendency to re-contextualize, thus domesticate or neutralise the original message to the Western audience. However, this has come at the expense of dehistoricising, deideologising and depoliticising the original, leading to a more culturally/contextually universal translation that seems to be drifted into the more dominant and valued Anglo-American and European cultures. These changes could be related to Kilpatrick’s lack of information, or interest, in the decades-long struggle between Israelis and Palestinians, so a neutral stance may have sounded a safer option to her. It could also be related to her belief that Kanafani’s novel should not be politicised, instead focusing our attention more on its plot structure and characters. Personally, I am of the opinion that Kilpatrick has created a more contextually homogenised text only to maintain relevance to a widely diverse audience.